Análisis del stock de empresas de Loreto inscritas como personas naturales periodo 2020 – 2024 - Del Aguila Malaverry, Elvis Ronald (2025)
Companies incorporated as individuals make up the largest segment of the business population operating in Loreto. These are small businesses that do not require large capital to open and operate; however, they are the main generator of employment. This research analyzes the historical behavior of registered companies over five years, studying the trend sequence of their behavior. Hence, it is classified as Descriptive and of Non-Experimental design. It is concluded that the stock of companies in Loreto, registered as individuals, had variable behavior (-115.08%) during the five-year period 2020–2024, when the ideal would have been for it to grow year after year as a sign of increasing economic dynamics. Registered companies also showed variable behavior similar to the stock, with increases and decreases during the years of analysis. The registered companies highlight having had a female leader in the majority (55.56%), which demonstrates the entrepreneurial spirit of women compared to men (44.44%), showing their decisiveness in taking on challenges. Finally, the analysis of the deregistered companies highlights that those led by men (52.18%) were the ones that mostly withdrew from the activity compared to those led by women (47.82%), highlighting the efficiency of the latter.